The Text-Building Functions of Word-Forming Elements - Vasyl Greshchuk (Vasyl Stefanyk Precarpathian National University, 2020)
The article discusses the role of word formation in text production. It is argued that word-forming elements can perform various functions connected with text production. Derivational elements serve as starting structural and semantic material for textual categories; they create local and global textual connections; allow for an unambiguous representation of information thus eliminating cumbersomeness and syntactic overload; enable textual progression; and contribute to generating textual connotations. Word-forming elements (both basic and complex ones) perform different text-oriented functions